Formyl peptide receptor-1 (FPR1) represses intestinal oncogenesis - Julie Le Naour; Léa Montégut; Yuhong Pan; Sarah Adriana Scuderi; Pierre Cordier; Adrien Joseph; Allan Sauvat; Valerio Iebba; Juliette Paillet; Gladys Ferrere; Ludivine Brechard; Claire Mulot; et al. (OncoImmunology)
Formyl peptide receptor-1 (FPR1) is a pattern recognition receptor that is mostly expressed by myeloid cells. In patients with colorectal cancer (CRC), a loss-of-function polymorphism (rs867228) in the gene coding for FPR1 has been associated with reduced responses to chemotherapy or chemoradiotherapy. Moreover, rs867228 is associated with accelerated esophageal and colorectal carcinogenesis. Here, we show that dendritic cells from Fpr1−/− mice exhibit reduced migration in response to chemotherapy-treated CRC cells. Moreover, Fpr1−/− mice are particularly susceptible to chronic ulcerative colitis and colorectal oncogenesis induced by the mutagen azoxymethane followed by oral dextran sodium sulfate, a detergent that induces colitis. These experiments were performed after initial co-housing of Fpr1−/− mice and wild-type controls, precluding major Fpr1-driven differences in the microbiota. Pharmacological inhibition of Fpr1 by cyclosporin H also tended to increase intestinal oncogenesis in mice bearing the ApcMin mutation, and this effect was reversed by the anti-inflammatory drug sulindac. We conclude that defective FPR1 signaling favors intestinal tumorigenesis through the modulation of the innate inflammatory/immune response.